Psycho‐educational interventions focused on maternal or infant sleep for pregnant women to prevent the onset of antenatal and postnatal depression: A systematic review. Issue 1 (19th December 2020) - Sasaki, Natsu; Yasuma, Naonori; Obikane, Erika; Narita, Zui; Sekiya, Junpei; Inagawa, Takuma; Nakajima, Aiichiro; Yamada, Yuji; Yamazaki, Ryuichi; Matsunaga, Asami; Saito, Tomomi; Imamura, Kotaro; et al.
Abstract: Aims: This systematic review aimed to evaluate randomized controlled trials (RCTs) to examine the effect of maternal and infant sleep intervention during women's pregnancy for the purpose of preventing perinatal depression. Method: A systematic search (from inception to January 28, 2019) for RCTs using five electronic databases—the Cochrane Controlled Register of Trials (CENTRAL), Embase, PubMed, PsycINFO, and Ichushi Web (Japan Medical Abstracts Society)—was conducted. Twelve investigators independently conducted initial screenings based on title and abstract, and then, two researchers performed full‐text reviews one by one. A meta‐analysis would be conducted if at least three studies were found. However, only two articles that met inclusion criteria, and narrative data synthesis was conducted for these two articles. The study protocol has been registered at PROSPERO (CRD42019119999). Result: A total of 13 654 studies were initially searched. After removing duplicates, 10 547 studies were screened, and finally, two studies met the inclusion criteria. In both studies, the intervention was a one‐time face‐to‐face session during pregnancy to deliver the behavioral knowledge and skills for optimizing sleep hygiene for both infant and mother. Effectiveness of the intervention in improving maternal mood was not significant in one study. In the other, there was a significant difference in maternal mood between the intervention and control group. No mood comparison was made between baseline and postintervention. Conclusion: This study found limited evidence to support the effectiveness of sleep intervention for all pregnant women, which means "universal intervention, " to protect maternal mental health. Further well‐designed RCTs are needed to confirm these findings. Abstract : This systematic review aimed to evaluate randomized controlled trials (RCTs) to examine the effect of maternal and infant sleep intervention during women's pregnancy to prevent perinatal depression. Two studies that met the criteria were not yielded a consistent conclusion on effectiveness. Further well‐designed RCTs are needed to confirm these findings.